Research at Undergraduate Level: Medical Student's Perspective - Rohini Motwani; Vivek Hada; Deepika G; Madhuri Taranikanti (Dr. Annil Mahajan, 2021)
Background: Research can be defined as scientific and systemic search for pertinent information on a specific topic. Medical research is essential to address the health problems and needs of the community and to enhance the knowledge of the students to translate into better health care. Aims and objectives: The objective of our study is to know the perspective of the medical students towards research and to enlist the factors influencing these attitudes. Material and Methods: A cross‑sectional study was conducted using pee-designed questionnaire that was validated and circulated through online Google forms. Undergraduate medical students of three academic years (2016, 2017, 2018) were the participants. The questionnaire was prepared after reviewing similar studies done previously. Results: Two hundred and ninety-two (292) students participated voluntarily in the study. 79.8% of the students showed interest in research. Most common reason cited was improvement in reasoning ability and gaining of deeper knowledge. It was observed that 20% of the respondents were involved in some research projects and most of them showed interest in pursuing research in future. Conclusion: Research projects can help students to develop critical analysis skills. Involvement in research will help them to understand the significance of it in finding the solutions to health problems. And in the process, it will enable them to gain deeper understanding of the process and will improve their writing skills and disseminate the knowledge through publication. The diverse burden of disease within India requires physician-scientists to emerge out of future generations of health care professionals.